Teacher Digital Competence: A Bibliometric Analysis of Global Research Trends - Loso Judijanto (Westscience Press, 2026)
The quick progress of digital technologies has significantly changed education processes and increased the necessity for teachers to have enough digital skills. Teacher digital competence has become one of the important issues to be researched with an emphasis put on digital technologies integration into the process of teaching, assessment, professional development, and learning. This study is devoted to analyzing the global trends in researches, intellectual structure, major contributions, and new research directions concerning the issue of teacher digital competence through the bibliometric analysis method. The data were collected in the Scopus database with the use of appropriate keywords linked to teacher digital competence, digital literacy, digital skills, and educational technologies. The publications were analyzed by means of bibliometric methods like performance analysis, citation analysis, keyword co-occurrence analysis, density visualization, thematic evolution, and collaboration networks analysis with the use of VOSviewer. The results prove a significant trend of the increasing interest to the problem of teacher digital competence, especially since the beginning of the COVID-19 pandemic when more and more online and technology-enhanced learning became common. It is possible to state that the major research themes include digital competence, digital literacy, teacher training, e-learning, digital transformation, and technology integration. Citation analysis highlights influential studies focusing on digital competence frameworks, teacher readiness, and digital transformation in education, while collaboration analysis identifies Spain and several European countries as major contributors to global knowledge development. Recent trends indicate a growing research interest in artificial intelligence, digital tools, and innovative learning systems. This study contributes to the existing literature by mapping the evolution of teacher digital competence research and identifying future research directions related to sustainable digital education, AI-supported teaching, and equitable access to digital learning environments.